2001
DOI: 10.1148/radiology.218.2.r01ja32402
|View full text |Cite
|
Sign up to set email alerts
|

Digital Radiography of Scoliosis with a Scanning Method: Initial Evaluation

Abstract: The described digital scanning method has acceptable image quality and adequate accuracy in angle measurements. The radiation dose required for digital exposure imaging is higher than that required for screen-film imaging, but that required for digital fluoroscopy is much lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 19 publications
3
88
1
5
Order By: Relevance
“…However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4). Analysing these previous studies it can be shown that most authors choose scoliotic curves smaller than 40°which may not reflect the true every day clinical situation [4] ( Table 1). Sixty percent of our patients had curve angles of more than 60°, whereas most of the former studies investigated curves between 20°and 40° [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4). Analysing these previous studies it can be shown that most authors choose scoliotic curves smaller than 40°which may not reflect the true every day clinical situation [4] ( Table 1). Sixty percent of our patients had curve angles of more than 60°, whereas most of the former studies investigated curves between 20°and 40° [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…It is an objective measure and is generally used to make decisions about the progression of a curve, as well as the need and success of treatment. Measurements of the Cobb angle bare an intra-and interobserver variability of approximately 4°to 8° [2,[4][5][6]. Sources of error are a wrong definition of end vertebra, an incorrect drawing of the lines through endplates or through the pedicles, drawing of perpendiculars or the measurement of the angle itself.…”
Section: Introductionmentioning
confidence: 99%
“…To take advantage of lower radiation exposure for our patients provided by digital techniques we stopped using conventional films in our clinical routine. Further optimization of digital fluoroscopy technique may result in an additional dose reduction for patients with AIS and an improved image quality [3].…”
Section: Discussionmentioning
confidence: 99%
“…with AIS [2]. However, digital fluoroscopy has also limitations, such as horizontal bars and patient motion during exposure with resulting artefacts (Fig.…”
Section: Torsten Kluba Ju¨rgen Scha¨fer Tobias Hahnfeldt Thomas Niemeyermentioning
confidence: 99%
See 1 more Smart Citation